2023
DOI: 10.3390/antibiotics12040747
|View full text |Cite
|
Sign up to set email alerts
|

Complex Networks Analyses of Antibiofilm Peptides: An Emerging Tool for Next-Generation Antimicrobials’ Discovery

Abstract: Microbial biofilms cause several environmental and industrial issues, even affecting human health. Although they have long represented a threat due to their resistance to antibiotics, there are currently no approved antibiofilm agents for clinical treatments. The multi-functionality of antimicrobial peptides (AMPs), including their antibiofilm activity and their potential to target multiple microbes, has motivated the synthesis of AMPs and their relatives for developing antibiofilm agents for clinical purposes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“… Aguilera-Mendoza et al (2019) provided a detailed explanation of this module, and further information is available in the online documentation of the software ( https://grupo-medicina-molecular-y-traslacional.github.io/StarPep_doc/networks.html ). In addition, specific use cases have been reported by Ayala-Ruano et al (2022) , Romero et al (2022) , Castillo-Mendieta et al (2023) , and Agüero-Chapin et al (2023) .…”
Section: Software Modulesmentioning
confidence: 99%
See 1 more Smart Citation
“… Aguilera-Mendoza et al (2019) provided a detailed explanation of this module, and further information is available in the online documentation of the software ( https://grupo-medicina-molecular-y-traslacional.github.io/StarPep_doc/networks.html ). In addition, specific use cases have been reported by Ayala-Ruano et al (2022) , Romero et al (2022) , Castillo-Mendieta et al (2023) , and Agüero-Chapin et al (2023) .…”
Section: Software Modulesmentioning
confidence: 99%
“…These important nodes facilitate the identification of shared motifs among potential AMP families organized into distinct communities. Previous research identified such motifs for different AMPs, including antiparasitic ( Ayala-Ruano et al 2022 ), tumor-homing ( Romero et al 2022 ), hemolytic ( Castillo-Mendieta et al 2023 ), and antibiofilm peptides ( Agüero-Chapin et al 2023 ). In addition, these nodes serve as the basis for the subsequent creation of mQSSMs, as detailed in the next section.…”
Section: Software Modulesmentioning
confidence: 99%
“…Our method is based on complex network science and multiquery similarity searching (MQSS) models. This procedure has demonstrated not only to accurately predict tumor-homing and antiparasitic peptide activities but also to get a deeper insight into the peptide chemical space, , hence improving peptide-based drug design. Furthermore, a software specifically designed for this purpose, named StarPep toolbox v0.8.5 has been developed to facilitate the workflow …”
Section: Introductionmentioning
confidence: 99%
“…Machine learning models have emerged as a time-saving and cost-effective tool for screening large data sets to identify potential AMPs. To date, machine learning models based on amino acid sequences have mainly been built using traditional and deep learning (DL) techniques, as well as using similarity networks. , However, the outstanding results of deep neural network-based approaches, such as trRosetta, AlphaFold, RoseTTAFold, ESMFold, and HelixFold-Single, in the prediction of tertiary (3D) structures of proteins from their amino acid sequences have unlocked new opportunities to build better predictive models. In this regard, non-DL based models using 3D protein descriptors as well as Graph Neural Network-based models , (e.g., equivariant network) are promissory strategies to be developed.…”
Section: Introductionmentioning
confidence: 99%